Manufacturing method of electromagnetic valve material high in corrosion resistance and easy to cut

By adding nickel and titanium to stainless steel and using tin bismuth alloy deteriorator and nickel electroplating technology, the problem of insufficient corrosion resistance and strength of existing solenoid valve materials is solved, and a solenoid valve with high corrosion resistance and easy cutting is achieved Materials meet the needs of new energy vehicles.

CN119464614APending Publication Date: 2025-02-18JIANGSU MINGZHAN SPECIAL STEEL MFG CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411379162.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing solenoid valve materials have poor performance in corrosion resistance and strength, and cannot meet the demand for high-end stainless steel materials on extended-range engines of new energy vehicles.

Method used

By adding nickel and titanium to stainless steel and using tin bismuth alloy deterioration agent for deterioration treatment, as well as primary electroplating and secondary electroplating, a nickel layer is formed to improve the corrosion resistance and machinability of the material.

Benefits of technology

It realizes high corrosion resistance and easy cutting of stainless steel materials, improves the toughness, tensile strength and high temperature mechanical properties of the materials, and meets the needs of steel for solenoid valves in new energy vehicles.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a manufacturing method of an electromagnetic valve material with high corrosion resistance and easy cutting, which relates to the technical field of stainless steel and mainly comprises the following steps: melting in a heating furnace, AOD (argon oxygen decarburization) refining, LF (ladle furnace) refining, pouring, heat treatment, pretreatment, primary electroplating, secondary electroplating and finished product obtaining. And meanwhile, tin-bismuth alloy with specific content is introduced as a modifier for modification treatment, a slag former is added for refining and slagging-off, and the electromagnetic valve material which is good in corrosion resistance, high in strength and free of cutting is successfully prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel, in particular to a method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting. Background Art

[0002] A solenoid valve is a device that uses electromagnetic principles to control the flow of liquid or gas. The material selection has an important impact on the performance, reliability and service life of the solenoid valve. It needs to have good corrosion resistance, strength, magnetic permeability and good machinability. The commonly used stainless steel material is 430 stainless steel. In the prior art, in order to improve the machinability of 430 stainless steel, the sulfur content in 430 stainless steel is increased to improve the machinability of stainless steel, and 430F stainless steel is obtained. However, compared with other advanced stainless steels, its corrosion resistance and strength are not good. In recent years, new energy vehicles have developed rapidly in China, and the demand for steel for solenoid valves on range-extended engines has increased day by day. Existing solenoid valve materials cannot meet the requirements.

[0003] In summary, in order to solve the above problems, it is of great significance to provide a method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting. Summary of the invention

[0004] The object of the present invention is to provide a method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting, comprising the following steps: S1: Add base steel into an electric furnace for melting, add nickel powder, and perform electromagnetic stirring to obtain molten steel A; S2: Transfer molten steel A to an AOD refining furnace, add titanium powder, and refine under an inert gas atmosphere to obtain molten steel B; S3: Transfer the molten steel B to the LF furnace, add a modifier and perform a modification treatment under an inert gas atmosphere; add a slag-forming agent to refine and slag, perform nitrogen refining, and tap the steel to obtain molten steel C; S4: pouring molten steel C into the mold for casting, feeding the riser, keeping warm, demoulding; transferring to a heating furnace, heating to a constant temperature, rolling, and cooling naturally to obtain a round bar; S5: heat treating the round bar, cooling it in the furnace, and taking it out of the furnace to obtain an annealed round bar; S6: peeling the annealed round bar to the required size, straightening, ultrasonic flaw detection, and coreless grinding to the required size to obtain the primary product; S7: Grind the rough product, soak it in degreasing solution, soak it in hydrochloric acid solution, transfer it to electrolyte A for primary electroplating, soak it in hydrochloric acid solution; transfer it to electrolyte B for secondary electroplating, rinse it with deionized water, and obtain the solenoid valve material.

[0006] Preferably, the composition of the base steel includes the following substances, calculated by mass fraction: C: 0.02~0.03%, Mn: 0.4~0.7%, Si: 0.3~0.5%, P≤0.035, S: 0.16~0.20%, Cr: 17.4~18.5%, and the rest is Fe and unavoidable impurities.

[0007] Preferably, the nickel powder is added in an amount of 0.5-0.7wt% of the base steel; the titanium powder is added in an amount of 0.3-0.4wt% of the base steel; the modifier is added in an amount of 0.3-0.5wt% of the base steel; and the slag-forming agent is added in an amount of 3-4wt% of the base steel.

[0008] Preferably, the modifier comprises a tin-bismuth alloy; the slag-forming agent comprises the following substances, based on 100 parts by mass: 4 to 5 parts of magnesite, 12 to 15 parts of aluminum powder, 5 to 8 parts of fluorite powder, and the rest is dolomite powder.

[0009] Preferably, the tin-bismuth alloy is Sn42Bi58.

[0010] Preferably, during the melting process in the electric furnace, the melting temperature is 1500-1600°C; during the electromagnetic stirring process, the stirring time is 1-2h; during the adding of titanium powder, the adding temperature is 1450-1550°C; during the refining process, the refining temperature is 1550-1580°C, and the refining time is 1-1.5h; during the modification process, the modification temperature is 1500-1550°C, and the modification time is 0.5-1h; during the nitrogen refining process, the nitrogen flow rate is 0.5-1m 2 / s, and the nitrogen refining time is 0.5-1h. In the steel tapping process, the steel tapping temperature is 1540-1560°C.

[0011] In the electromagnetic stirring process, the electromagnetic stirring speed is 250-300 rpm; in the nitrogen refining process, the nitrogen flow rate is 0.5-1 m 2 / s.

[0012] Preferably, during the insulation process, the insulation temperature is 350-400°C, and the insulation time is 10-12h; during the heating and constant temperature process, the furnace inlet temperature is 290-310°C, the heating end temperature is 1280-1320°C, and the constant temperature time is 2-2.5h; during the rolling process, the final rolling temperature is 950-1050°C.

[0013] Preferably, during the heat treatment process, the heat treatment temperature is 800-840°C and the heat treatment time is 4-6 hours; during the furnace-out process, the furnace-out temperature is 640-660°C.

[0014] The annealed round rod has a HB of 148-152, and the primary product has a h9 tolerance, a straightness of 0.2 / 1000, and a surface roughness Ra of 0.6 μm.

[0015] Preferably, during the electroplating process, the electroplating temperature is 42-47°C and the current density is 0.04-0.05A / cm 2 , the electroplating time is 10-15min, the pH is 6.8-7.2; in the secondary electroplating process, the electroplating temperature is 40-43°C, and the current density is 0.045-0.05A / cm 2 , electroplating time is 15~20min, pH is 3.8~4.2.

[0016] Preferably, the electroplating thickness is 80-85 μm.

[0017] Preferably, the electrolyte A comprises the following substances: 140-145 g / L nickel sulfate hexahydrate, 120-125 g / L sodium citrate, 10-15 g / L sodium chloride, and 23-26 g / L boric acid; the electrolyte B comprises the following substances: 250-255 g / L nickel sulfate hexahydrate, 45-50 g / L nickel chloride hexahydrate, 45-50 g / L boric acid, 10-15 g / L benzotriazole, and 5-10 mL / L brightener N-11, and the solvent is deionized water.

[0018] The degreasing liquid comprises the following substances: 20-25 g / L sodium carbonate, 25-30 g / L sodium phosphate, 15-20 g / L sodium dodecylbenzene sulfonate, and the solvent is deionized water.

[0019] Compared with the prior art, the beneficial effects of this application include the following aspects: (1) The addition of nickel in the present invention can increase the plasticity of stainless steel, making it less prone to brittle fracture during processing and use, improving the toughness and ductility of the material, stabilizing the austenite structure, helping to improve the stability of the stainless steel structure, reducing the tendency of cold working hardening, and improving corrosion resistance. The added titanium can improve intergranular corrosion performance, can combine with carbon to form stable carbides, thereby preventing carbon from segregating at the grain boundaries, reducing the sensitivity of intergranular corrosion, and also helping to obtain a finer and more uniform grain structure, making the structure stable, improving the strength and toughness of the material, and enhancing the mechanical properties of stainless steel in high temperature environments.

[0020] (2) The present invention adds a modifier containing tin-bismuth alloy to the steelmaking process for modification. The addition of bismuth can make the micro-bismuth melt after contacting the cutting tool during the stainless steel cutting process, and play the role of lubricant, reduce friction and heat accumulation, thereby avoiding overheating during the cutting process, improving cutting efficiency and cutting quality, and thus improving production efficiency and processing accuracy. The surface of tin is more likely to form a dense and continuous oxide layer, and the zeta potential of tin is relatively high. After adding it to stainless steel, the corrosion resistance can be significantly improved.

[0021] (3) The sulfur content in free-cutting stainless steel is relatively high, and manganese mainly exists in the form of manganese sulfide. However, as a non-metallic inclusion, the long strip structure of manganese sulfide will destroy the continuity of the metal matrix, thereby forming stress concentration points during the rolling process. When subjected to external forces, these stress concentration points are likely to become the starting points of cracks, thereby inducing cracking. They are also sensitive points for pitting and crevice corrosion, and their corrosion resistance is reduced. Therefore, the bismuth introduced in the present invention can help the manganese sulfide to change from a long strip to a spherical shape, thereby improving the ductility of the stainless steel material, reducing the possibility of cracking during the rolling process, and improving the corrosion resistance in disguise. At the same time, the added tin will wrap the manganese sulfide, preventing it from contacting the outside world, reducing the possibility of becoming a pitting sensitive point, and further improving the corrosion resistance of the stainless steel material. The ratio of the tin-bismuth alloy used in the present invention can keep the bismuth content within a reasonable range, that is, preventing the problem of bismuth being too large or unevenly distributed in the second phase of the steel, resulting in a decrease in strength. At the same time, this alloy ratio can also meet the requirement of tin wrapping manganese sulfide. At the same time, the excess tin can further improve the corrosion resistance of the stainless steel.

[0022] (4) The present invention electroplates a layer of nickel on the surface of stainless steel, further improving the corrosion resistance of stainless steel and extending its service efficiency. The nickel-plated layer can reduce the friction and wear between the cutting tool and the stainless steel substrate to a certain extent, reduce cutting resistance, and improve processing efficiency. At the same time, nickel sulfate is used for primary electroplating to form a transition layer on the surface of stainless steel, which buffers corrosion and improves the bonding degree with stainless steel; nickel chloride is used for secondary electroplating, and such an electroplated layer is tighter and can effectively isolate the corrosive medium from the outside. Benzotriazole is also added as a rust inhibitor to further improve the corrosion resistance of stainless steel, and a brightener is added to improve the smoothness of the stainless steel material and reduce the retention of the corrosive medium. DETAILED DESCRIPTION

[0023] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0024] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplarily include: nickel powder, purity 99.9%, particle size 600~800 mesh, provided by Zhejiang Yamei Nano Technology Co., Ltd.; titanium powder, purity 99%, particle size 600~800 mesh, provided by Nanjing Chemical Reagent Co., Ltd.; tin-bismuth alloy, purity 99%, provided by Sichuan Juchun Materials Technology Co., Ltd.; magnesite, purity 99%, provided by Shanghai Yuanye Biotechnology Co., Ltd.; fluorite powder, purity 99%, provided by Wuhan Chujiang Haoyu Chemical Technology Development Co., Ltd.; dolomite powder, purity 99%, provided by Wuhan Jiyesheng Chemical Co., Ltd.; nickel sulfate hexahydrate, purity 99%, provided by Shandong Xinhe New Materials Co., Ltd.; nickel chloride hexahydrate, purity 99%, provided by Shandong Xinheng Chemical Co., Ltd.; benzotriazole, purity 99%, provided by Wuhan Amidexiang Chemical Co., Ltd.; brightener N-11, purity 99%, provided by Wuhan Penglei Biotechnology Co., Ltd.

[0025] In the following embodiments, the base steel includes the following components, calculated by mass fraction: C: 0.023%, Mn: 0.56%, Si: 0.34%, P≤0.035, S: 0.17%, Cr: 18.1%, and the rest is Fe and unavoidable impurities; parts are by mass, and the raw materials are all commercially available.

[0026] Embodiment 1: A method for preparing a solenoid valve material with high corrosion resistance and easy cutting comprises the following steps: S1: melt the base steel in an electric furnace at 1550°C, add 0.6wt% nickel powder to the base steel, and stir at 250rpm for 1.5h to obtain molten steel A; S2: Transfer molten steel A to an AOD refining furnace, add 0.35wt% titanium powder of base steel at 1500℃, and refine at 1560℃ for 1.5h in an argon atmosphere to obtain molten steel B; S3: Transfer molten steel B to LF furnace, add 0.4wt% modifier of base steel in nitrogen atmosphere, and perform modification at 1520℃ for 0.5h; add 3.5wt% slag-making agent (4.5 parts of magnesite, 13.5 parts of aluminum powder, 6 parts of fluorite powder, 76 parts of dolomite powder) of base steel, and heat at 0.5m 2 / s, nitrogen was introduced for nitrogen refining for 1 hour to obtain molten steel C; S4: The molten steel C is tapped at 1550°C, poured into a preheated mold for casting, the riser is fed for shrinkage, kept at 350°C for 12 hours, and demolded; the molten steel C is transferred to a heating furnace, the furnace temperature is 300°C, the temperature is gradually increased to 1300°C, the temperature is kept constant for 2 hours, rolling is started, the final rolling temperature is 1000°C, and the round bar is obtained by natural cooling; S5: heat treating the round bar at 820°C for 5h, cooling naturally along with the furnace, and removing the round bar from the furnace after the temperature of the round bar is reduced to 650°C, thereby obtaining an annealed round bar; S6: peeling the annealed round bar to the required size, straightening, ultrasonic flaw detection, and coreless grinding to the required size to obtain the primary product; S7: After the rough product is polished, it is soaked in a degreasing solution (25 g / L sodium carbonate, 25 g / L sodium phosphate, 15 g / L sodium dodecylbenzene sulfonate) for 5 min, rinsed with deionized water, soaked in a 2.5% hydrochloric acid solution for 15 s, taken out and rinsed with deionized water, and transferred to electrolyte A (140 g / L nickel sulfate hexahydrate, 125 g / L sodium citrate, 15 g / L sodium chloride, 24 g / L boric acid) at 45 °C, pH 7, and 0.045 A / cm 2 Electroplating was performed for 15 min at a time. After rinsing with deionized water, the samples were immersed in a 2.5% hydrochloric acid solution for 15 s, rinsed with deionized water, and transferred to electrolyte B (255 g / L nickel sulfate hexahydrate, 50 g / L nickel chloride hexahydrate, 45 g / L boric acid, 10 g / L benzotriazole, 5 mL / L brightener N-11) at 42 °C, pH 4, and 0.05 A / cm 2 The secondary electroplating was performed for 15 minutes, and the product was rinsed with deionized water to obtain the solenoid valve material.

[0027] Embodiment 2: A method for preparing a solenoid valve material with high corrosion resistance and easy cutting comprises the following steps: S1: melt the base steel in an electric furnace at 1500°C, add 0.5wt% nickel powder to the base steel, and stir with electromagnetic stirring at 250rpm for 1h to obtain molten steel A; S2: Transfer molten steel A to an AOD refining furnace, add 0.3wt% titanium powder of base steel at 1450℃, and refine at 1550℃ for 1h under argon atmosphere to obtain molten steel B; S3: Transfer molten steel B to LF furnace, add 0.3wt% modifier of base steel in nitrogen atmosphere, and perform modification at 1500℃ for 0.5h; add 3wt% slag-making agent (4 parts of magnesite, 12 parts of aluminum powder, 5 parts of fluorite powder, 79 parts of dolomite powder) of base steel, and heat the furnace at 0.5m 2 / s, nitrogen was introduced for nitrogen refining for 0.5h to obtain molten steel C; S4: The molten steel C is tapped at 1540°C, poured into a preheated mold for casting, the riser is fed for shrinkage, kept at 350°C for 10 hours, and demolded; transferred to a heating furnace, the furnace temperature is 290°C, gradually heated to 1280°C, kept at a constant temperature for 2 hours, and rolled, the final rolling temperature is 950°C, and naturally cooled to obtain a round bar; S5: heat treating the round bar at 800°C for 4h, cooling naturally along with the furnace, and the temperature of the round bar is reduced to 640°C before being taken out of the furnace to obtain an annealed round bar; S6: peeling the annealed round bar to the required size, straightening, ultrasonic flaw detection, and coreless grinding to the required size to obtain the primary product; S7: After the rough product is polished, it is soaked in a degreasing solution (20 g / L sodium carbonate, 25 g / L sodium phosphate, 15 g / L sodium dodecylbenzene sulfonate) for 5 min, rinsed with deionized water, soaked in a 2% hydrochloric acid solution for 10 s, taken out and rinsed with deionized water, and transferred to electrolyte A (140 g / L nickel sulfate hexahydrate, 120 g / L sodium citrate, 10 g / L sodium chloride, 23 g / L boric acid) at 42 °C, pH 6.8 and 0.04 A / cm 2 The samples were electroplated for 10 min at a time. After being rinsed with deionized water, they were immersed in a 2% hydrochloric acid solution for 10 s, rinsed with deionized water, and transferred to electrolyte B (250 g / L nickel sulfate hexahydrate, 45 g / L nickel chloride hexahydrate, 45 g / L boric acid, 10 g / L benzotriazole, 5 mL / L brightener N-11) at 40 °C, pH 3.8, and 0.045 A / cm 2 The secondary electroplating was performed for 15 minutes, and the product was rinsed with deionized water to obtain the solenoid valve material.

[0028] Embodiment 3: A method for preparing a solenoid valve material with high corrosion resistance and easy cutting comprises the following steps: S1: melt the base steel in an electric furnace at 1600°C, add 0.7wt% nickel powder to the base steel, and stir at 300rpm for 2h to obtain molten steel A; S2: Transfer molten steel A to an AOD refining furnace, add 0.4wt% titanium powder of base steel at 1550℃, and refine at 1580℃ for 1.5h in an argon atmosphere to obtain molten steel B; S3: Transfer molten steel B to LF furnace, add 0.5wt% modifier of base steel in nitrogen atmosphere, and perform modification at 1550℃ for 1h; add 4wt% slag-making agent (5 parts of magnesite, 15 parts of aluminum powder, 8 parts of fluorite powder, 72 parts of dolomite powder) of base steel at 1m 2 / s, nitrogen was introduced for nitrogen refining for 1 hour to obtain molten steel C; S4: The molten steel C is tapped at 1560°C, poured into a preheated mold for casting, the riser is fed for shrinkage, kept at 400°C for 12 hours, and demolded; transferred to a heating furnace, the furnace temperature is 310°C, gradually heated to 1320°C, kept at a constant temperature for 2.5 hours, and rolled, the final rolling temperature is 1050°C, and naturally cooled to obtain a round bar; S5: heat treating the round bar at 840°C for 6h, cooling naturally along with the furnace, and the temperature of the round bar is reduced to 660°C before being taken out of the furnace to obtain an annealed round bar; S6: peeling the annealed round bar to the required size, straightening, ultrasonic flaw detection, and coreless grinding to the required size to obtain the primary product; S7: After the rough product is polished, it is soaked in a degreasing solution (25 g / L sodium carbonate, 30 g / L sodium phosphate, 20 g / L sodium dodecylbenzene sulfonate) for 10 min, rinsed with deionized water, soaked in a 3% hydrochloric acid solution for 20 s, taken out and rinsed with deionized water, and transferred to electrolyte A (145 g / L nickel sulfate hexahydrate, 125 g / L sodium citrate, 15 g / L sodium chloride, 26 g / L boric acid) at 47 °C, pH 7.2 and 0.05 A / cm 2 Electroplating was performed for 15 min at a time. After rinsing with deionized water, the samples were immersed in a 3% hydrochloric acid solution for 20 s, rinsed with deionized water, and transferred to electrolyte B (255 g / L nickel sulfate hexahydrate, 50 g / L nickel chloride hexahydrate, 50 g / L boric acid, 15 g / L benzotriazole, 10 mL / L brightener N-11) at 43 °C, pH 4.2, and 0.05 A / cm 2 The secondary electroplating was performed for 20 minutes, and the product was rinsed with deionized water to obtain the solenoid valve material.

[0029] Comparative Example 1: Based on Example 1, titanium powder is not introduced and the other processes remain unchanged.

[0030] S1: melt the base steel in an electric furnace at 1550°C, add 0.6wt% nickel powder to the base steel, and stir at 250rpm for 1.5h to obtain molten steel A; S2: Transfer molten steel A to an AOD refining furnace and refine it at 1560°C for 1.5 h under an argon atmosphere to obtain molten steel B; S3: Transfer molten steel B to LF furnace, add 0.4wt% modifier of base steel in nitrogen atmosphere, and perform modification at 1520℃ for 0.5h; add 3.5wt% slag-making agent (4.5 parts of magnesite, 13.5 parts of aluminum powder, 6 parts of fluorite powder, 76 parts of dolomite powder) of base steel, and heat at 0.5m 2 / s, nitrogen was introduced for nitrogen refining for 1 hour to obtain molten steel C; S4: The molten steel C is tapped at 1550°C, poured into a preheated mold for casting, the riser is fed for shrinkage, kept at 350°C for 12 hours, and demolded; the molten steel C is transferred to a heating furnace, the furnace temperature is 300°C, the temperature is gradually increased to 1300°C, the temperature is kept constant for 2 hours, rolling is started, the final rolling temperature is 1000°C, and the round bar is obtained by natural cooling; S5: heat treating the round bar at 820°C for 5h, cooling naturally along with the furnace, and removing the round bar from the furnace after the temperature of the round bar is reduced to 650°C, thereby obtaining an annealed round bar; S6: peeling the annealed round bar to the required size, straightening, ultrasonic flaw detection, and coreless grinding to the required size to obtain the primary product; S7: After the rough product is polished, it is soaked in a degreasing solution (25 g / L sodium carbonate, 25 g / L sodium phosphate, 15 g / L sodium dodecylbenzene sulfonate) for 5 min, rinsed with deionized water, soaked in a 2.5% hydrochloric acid solution for 15 s, taken out and rinsed with deionized water, and transferred to electrolyte A (140 g / L nickel sulfate hexahydrate, 125 g / L sodium citrate, 15 g / L sodium chloride, 24 g / L boric acid) at 45 °C, pH 7, and 0.045 A / cm 2 Electroplating was performed for 15 min at a time. After rinsing with deionized water, the samples were immersed in a 2.5% hydrochloric acid solution for 15 s, rinsed with deionized water, and transferred to electrolyte B (255 g / L nickel sulfate hexahydrate, 50 g / L nickel chloride hexahydrate, 45 g / L boric acid, 10 g / L benzotriazole, 5 mL / L brightener N-11) at 42 °C, pH 4, and 0.05 A / cm 2 The secondary electroplating was performed for 15 minutes, and the product was rinsed with deionized water to obtain the solenoid valve material.

[0031] Comparative Example 2: Based on Example 1, no modifier was added and the other processes remained unchanged.

[0032] S1: melt the base steel in an electric furnace at 1550°C, add 0.6wt% nickel powder to the base steel, and stir at 250rpm for 1.5h to obtain molten steel A; S2: Transfer molten steel A to an AOD refining furnace, add 0.35wt% titanium powder of base steel at 1500℃, and refine at 1560℃ for 1.5h in an argon atmosphere to obtain molten steel B; S3: Transfer molten steel B to the LF furnace, add 3.5wt% of slag-making agent (4.5 parts of magnesite, 13.5 parts of aluminum powder, 6 parts of fluorite powder, and 76 parts of dolomite powder) of base steel under nitrogen atmosphere, and heat the molten steel to 0.5m 2 / s, nitrogen was introduced for nitrogen refining for 1 hour to obtain molten steel C; S4: The molten steel C is tapped at 1550°C, poured into a preheated mold for casting, the riser is fed for shrinkage, kept at 350°C for 12 hours, and demolded; the molten steel C is transferred to a heating furnace, the furnace temperature is 300°C, the temperature is gradually increased to 1300°C, the temperature is kept constant for 2 hours, rolling is started, the final rolling temperature is 1000°C, and the round bar is obtained by natural cooling; S5: heat treating the round bar at 820°C for 5h, cooling naturally along with the furnace, and removing the round bar from the furnace after the temperature of the round bar is reduced to 650°C, thereby obtaining an annealed round bar; S6: peeling the annealed round bar to the required size, straightening, ultrasonic flaw detection, and coreless grinding to the required size to obtain the primary product; S7: After the rough product is polished, it is soaked in a degreasing solution (25 g / L sodium carbonate, 25 g / L sodium phosphate, 15 g / L sodium dodecylbenzene sulfonate) for 5 min, rinsed with deionized water, soaked in a 2.5% hydrochloric acid solution for 15 s, taken out and rinsed with deionized water, and transferred to electrolyte A (140 g / L nickel sulfate hexahydrate, 125 g / L sodium citrate, 15 g / L sodium chloride, 24 g / L boric acid) at 45 °C, pH 7, and 0.045 A / cm 2 Electroplating was performed for 15 min at a time. After rinsing with deionized water, the samples were immersed in a 2.5% hydrochloric acid solution for 15 s, rinsed with deionized water, and transferred to electrolyte B (255 g / L nickel sulfate hexahydrate, 50 g / L nickel chloride hexahydrate, 45 g / L boric acid, 10 g / L benzotriazole, 5 mL / L brightener N-11) at 42 °C, pH 4, and 0.05 A / cm 2 The secondary electroplating was performed for 15 minutes, and the product was rinsed with deionized water to obtain the solenoid valve material.

[0033] Comparative Example 3: Based on Example 1, the modifier is changed to tin, and the other processes remain unchanged.

[0034] S1: melt the base steel in an electric furnace at 1550°C, add 0.6wt% nickel powder to the base steel, and stir at 250rpm for 1.5h to obtain molten steel A; S2: Transfer molten steel A to an AOD refining furnace, add 0.35wt% titanium powder of base steel at 1500℃, and refine at 1560℃ for 1.5h in an argon atmosphere to obtain molten steel B; S3: The molten steel B was transferred to the LF furnace, and 0.23wt% of bismuth powder (provided by Sichuan Liuzu Semiconductor Materials Co., Ltd.) was added to the base steel under nitrogen atmosphere, and the base steel was subjected to a modification treatment at 1520℃ for 0.5h; 3.5wt% of slag-making agent (4.5 parts of magnesite, 13.5 parts of aluminum powder, 6 parts of fluorite powder, and 76 parts of dolomite powder) was added to the base steel at 0.5m 2 / s, nitrogen was introduced for nitrogen refining for 1 hour to obtain molten steel C; S4: The molten steel C is tapped at 1550°C, poured into a preheated mold for casting, the riser is fed for shrinkage, kept at 350°C for 12 hours, and demolded; the molten steel C is transferred to a heating furnace, the furnace temperature is 300°C, the temperature is gradually increased to 1300°C, the temperature is kept constant for 2 hours, rolling is started, the final rolling temperature is 1000°C, and the round bar is obtained by natural cooling; S5: heat treating the round bar at 820°C for 5h, cooling naturally along with the furnace, and removing the round bar from the furnace after the temperature of the round bar is reduced to 650°C, thereby obtaining an annealed round bar; S6: peeling the annealed round bar to the required size, straightening, ultrasonic flaw detection, and coreless grinding to the required size to obtain the primary product; S7: After the rough product is polished, it is soaked in a degreasing solution (25 g / L sodium carbonate, 25 g / L sodium phosphate, 15 g / L sodium dodecylbenzene sulfonate) for 5 min, rinsed with deionized water, soaked in a 2.5% hydrochloric acid solution for 15 s, taken out and rinsed with deionized water, and transferred to electrolyte A (140 g / L nickel sulfate hexahydrate, 125 g / L sodium citrate, 15 g / L sodium chloride, 24 g / L boric acid) at 45 °C, pH 7, and 0.045 A / cm 2 Electroplating was performed for 15 min at a time. After rinsing with deionized water, the samples were immersed in a 2.5% hydrochloric acid solution for 15 s, rinsed with deionized water, and transferred to electrolyte B (255 g / L nickel sulfate hexahydrate, 50 g / L nickel chloride hexahydrate, 45 g / L boric acid, 10 g / L benzotriazole, 5 mL / L brightener N-11) at 42 °C, pH 4, and 0.05 A / cm 2 The secondary electroplating was performed for 15 minutes, and the product was rinsed with deionized water to obtain the solenoid valve material.

[0035] Comparative Example 4: Based on Example 1, only one electroplating is performed, and the other processes remain unchanged.

[0036] S1: melt the base steel in an electric furnace at 1550°C, add 0.6wt% nickel powder to the base steel, and stir at 250rpm for 1.5h to obtain molten steel A; S2: Transfer molten steel A to an AOD refining furnace, add 0.35wt% titanium powder of base steel at 1500℃, and refine at 1560℃ for 1.5h in an argon atmosphere to obtain molten steel B; S3: Transfer molten steel B to LF furnace, add 0.4wt% modifier of base steel in nitrogen atmosphere, and perform modification at 1520℃ for 0.5h; add 3.5wt% slag-making agent (4.5 parts of magnesite, 13.5 parts of aluminum powder, 6 parts of fluorite powder, 76 parts of dolomite powder) of base steel, and heat at 0.5m 2 / s, nitrogen was introduced for nitrogen refining for 1 hour to obtain molten steel C; S4: The molten steel C is tapped at 1550°C, poured into a preheated mold for casting, the riser is fed for shrinkage, kept at 350°C for 12 hours, and demolded; the molten steel C is transferred to a heating furnace, the furnace temperature is 300°C, the temperature is gradually increased to 1300°C, the temperature is kept constant for 2 hours, rolling is started, the final rolling temperature is 1000°C, and the round bar is obtained by natural cooling; S5: heat treating the round bar at 820°C for 5h, cooling naturally along with the furnace, and removing the round bar from the furnace after the temperature of the round bar is reduced to 650°C, thereby obtaining an annealed round bar; S6: peeling the annealed round bar to the required size, straightening, ultrasonic flaw detection, and coreless grinding to the required size to obtain the primary product; S7: After the rough product is polished, it is soaked in a degreasing solution (25 g / L sodium carbonate, 25 g / L sodium phosphate, 15 g / L sodium dodecylbenzene sulfonate) for 5 min, rinsed with deionized water, soaked in a 2.5% hydrochloric acid solution for 15 s, taken out and rinsed with deionized water, and transferred to electrolyte A (140 g / L nickel sulfate hexahydrate, 125 g / L sodium citrate, 15 g / L sodium chloride, 24 g / L boric acid) at 45 °C, pH 7, and 0.045 A / cm 2 The electroplating was performed for 15 minutes each time, and the samples were rinsed with deionized water to obtain the solenoid valve material.

[0037] Performance test: (1) Salt spray test: According to GB / T10125, each sample was placed in a 5% sodium chloride solution at a temperature of 35°C in a salt spray environment, and the appearance of the first rust point was observed. The rust time was measured. The experimental data are shown in Table 1; (2) Tensile strength: According to GB / T228.1-2010, the tensile strength of each sample was tested using a universal mechanical testing machine. The experimental data are shown in Table 1; Table 1 project Corrosion time / h Tensile strength / MPa Example 1 182 555 Example 2 178 550 Example 3 175 540 Comparative Example 1 162 475 Comparative Example 2 144 485 Comparative Example 3 159 500 Comparative Example 4 155 510 Conclusion: It can be seen from Table 1 that in Comparative Example 1, titanium powder is not introduced, and it cannot be effectively combined with the contained carbon. Carbon is segregated at the grain boundaries, the corrosion resistance is reduced, and the stainless steel grains are not fine and uniform enough, and the tensile strength is reduced; in Comparative Example 2, no modifier is added. Due to the presence of long strips of manganese sulfide in the stainless steel, small cracks are generated during the rolling process, the corrosion resistance is greatly reduced, and the tensile strength is reduced; in Comparative Example 3, the modifier is changed to bismuth, and the other processes remain unchanged. Although the presence of bismuth transforms manganese sulfide into a spherical shape, the corrosion resistance is reduced due to the lack of tin wrapping; Comparative Example 4 only performs secondary electroplating, lacks the generated transition layer, has poor interface bonding, poor coating quality, and reduced corrosion resistance.

[0038] In summary, the present invention successfully prepares a solenoid valve material by adding titanium and nickel to stainless steel, using a tin-bismuth alloy modifier for modification, and electroplating the nickel layer once and twice, which has good cutting properties as well as good corrosion resistance and strength.

[0039] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting, characterized in that: The following steps are involved: S1: Add base steel into an electric furnace for melting, add nickel powder, and perform electromagnetic stirring to obtain molten steel A; S2: Transfer molten steel A to an AOD refining furnace, add titanium powder, and refine under an inert gas atmosphere to obtain molten steel B; S3: Transfer the molten steel B to the LF furnace, add a modifier and perform a modification treatment under an inert gas atmosphere; add a slag-forming agent to refine and slag, perform nitrogen refining, and tap the steel to obtain molten steel C; S4: pouring molten steel C into the mold for casting, feeding the riser, keeping warm, demoulding; transferring to a heating furnace, heating to a constant temperature, rolling, and cooling naturally to obtain a round bar; S5: heat treating the round bar, cooling it in the furnace, and taking it out of the furnace to obtain an annealed round bar; S6: peeling the annealed round bar to the required size, straightening, ultrasonic flaw detection, and coreless grinding to the required size to obtain the primary product; S7: Grind the rough product, soak it in degreasing solution, soak it in hydrochloric acid solution, transfer it to electrolyte A for primary electroplating, soak it in hydrochloric acid solution; transfer it to electrolyte B for secondary electroplating, rinse it with deionized water, and obtain the solenoid valve material.

2. The method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting according to claim 1, characterized in that: The composition of the basic steel includes the following substances, calculated by mass fraction: C: 0.02~0.03%, Mn: 0.4~0.7%, Si: 0.3~0.5%, P≤0.035, S: 0.16~0.20%, Cr: 17.4~18.5%, and the rest is Fe and unavoidable impurities.

3. The method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting according to claim 1, characterized in that: The nickel powder is added in an amount of 0.5-0.7wt% of the base steel; the titanium powder is added in an amount of 0.3-0.4wt% of the base steel; the modifier is added in an amount of 0.3-0.5wt% of the base steel; and the slag-forming agent is added in an amount of 3-4wt% of the base steel.

4. The method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting according to claim 1, characterized in that: The modifier includes tin-bismuth alloy; the slag-forming agent includes the following substances, calculated based on 100 parts by mass: 4 to 5 parts of magnesite, 12 to 15 parts of aluminum powder, 5 to 8 parts of fluorite powder, and the rest is dolomite powder.

5. The method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting according to claim 1, characterized in that: During the melting process in the electric furnace, the melting temperature is 1500-1600°C; during the electromagnetic stirring process, the stirring time is 1-2h; during the adding of titanium powder, the adding temperature is 1450-1550°C; during the refining process, the refining temperature is 1550-1580°C, and the refining time is 1-1.5h; during the modification process, the modification temperature is 1500-1550°C, and the modification time is 0.5-1h; during the nitrogen refining process, the nitrogen flow rate is 0.5-1m 2 / s, the nitrogen refining time is 0.5~1h; in the steel tapping process, the steel tapping temperature is 1540~1560℃.

6. The method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting according to claim 1, characterized in that: During the insulation process, the insulation temperature is 350-400°C and the insulation time is 10-12h; during the heating and constant temperature process, the furnace inlet temperature is 290-310°C, the heating end temperature is 1280-1320°C, and the constant temperature time is 2-2.5h; during the rolling process, the final rolling temperature is 950-1050°C.

7. The method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting according to claim 1, characterized in that: During the heat treatment process, the heat treatment temperature is 800-840° C. and the heat treatment time is 4-6 hours; during the furnace-out process, the furnace-out temperature is 640-660° C.

8. The method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting according to claim 1, characterized in that: During the electroplating process, the electroplating temperature is 42-47°C and the current density is 0.04-0.05A / cm 2 , the electroplating time is 10-15min, the pH is 6.8-7.2; in the secondary electroplating process, the electroplating temperature is 40-43°C, and the current density is 0.045-0.05A / cm 2 , electroplating time is 15~20min, pH is 3.8~4.

2.

9. The method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting according to claim 1, characterized in that: The electrolyte A comprises the following substances: 140-145 g / L nickel sulfate hexahydrate, 120-125 g / L sodium citrate, 10-15 g / L sodium chloride, and 23-26 g / L boric acid; the electrolyte B comprises the following substances: 250-255 g / L nickel sulfate hexahydrate, 45-50 g / L nickel chloride hexahydrate, 45-50 g / L boric acid, 10-15 g / L benzotriazole, and 5-10 mL / L brightener N-11, and the solvent is deionized water.

10. The solenoid valve material prepared according to the method for manufacturing a solenoid valve material with high corrosion resistance and easy cutting according to any one of claims 1 to 9.

Citation Information

Cited By

  • Precise stainless steel material for decoder and preparation method thereof

    CN120350287A

  • A precision stainless steel material for decoder and its preparation method

    CN120350287B